Speculative science ("fairy tale science") in physics, cosmology, and economics - Mattessich, Richard; Galassi, Giuseppe (De Computis, Revista Española de Historia de la Contabilidad., 2016)
The paper juxtaposes two recent books dealing with reality issues in a broad sense. The first of these, by Baggott (2013,) examines and criticizes the historically increasing trend to base scientific conclusions on mathematical hypotheses and logical consistency rather than on empirical evidence -- Bagott calls this trend “fairy tale science”. The second book, Tegmark (2014),i defends the opposite view – it considers Mathematics as identical to Reality and promotes increasing reliance of modern physics and cosmology on mathematical assumptions and logical consistencies rather than empirical evidence -- defending such controversial conclusions that we live in one of infinitely many parallel universes with numerous alter egos of each of us. But this is not a book review of Baggott (2013) and Tegmark (2014); its aim is to draw attention to the fact that social scientists are not the only scholars blamed for paying too much attention to model building and too little to empirical confirmation. This, ought to be of enormous interest to financial scholars; it may even be a consolation to some of them for emphasizing mathematical consistency rather than empirical confirmation. But our examples (from “speculative science” in finance) illustrate that such a trend caused staggering losses during the financial crisis of 1997-1998 (of Japan and Russia) and serious threats to the entire World Economic System during the crisis of 2007-2008